L’oralità in K. E. Kossi - Raffaele, Taddeo (TransCulturale, 2023)
The first part of this contribution focuses on the concepts of orality and oralitura, which Komla-Ebri ascribes to his literary writing. The second part discusses how orality has developed in Komla-Ebri’s writing as an imitative form of oral expression, where the values of the oral tradition are transmitted. Thanks to oralitura, the oral tradition is now expressed in the written form. Finally, the originality of Imbarazzismi is shown, his best-known published work. Following Bachtin’s theoretical hypotheses, these short stories can be ascribed to a sort of parody of the vulgarization of the Western culture.